The Impact of microfinance on poverty reduction through women’s empowerment - Chand, Prakash Bahadur (PT Mattawang Mediatama Solution, 2025)
This study investigates the impact of microfinance on women's empowerment and poverty reduction in Nepal's Kathmandu Valley. The research employs a mixed-methods approach, utilizing structured questionnaires with five-point Likert scales to collect data from 294 women participating in Self-Help Groups (SHGs), selected through purposive sampling. Descriptive and inferential statistical techniques, including Cronbach’s alpha reliability testing, ANOVA, regression, and correlation analysis, were applied to assess multidimensional outcomes. The results reveal that microfinance has the strongest positive impact on socioeconomic status (β=1.048, p<0.001), explaining 69.5% of empowerment variance (Adj. R²=0.695), while showing a negative association with household decision-making (β=-0.265, p<0.001). A key finding highlights the divergence between perceived financial benefits (mean scores 3.93-4.00) and their statistical insignificance in regression models (p=0.926), suggesting that economic interventions alone may be insufficient. The study demonstrates methodological rigor with high reliability (α>0.7) and robust multivariate analysis. The findings indicate that microfinance significantly influences socioeconomic empowerment but has complex effects on other dimensions of women's lives, underscoring the need for integrated approaches combining financial and social interventions.